ANALYSIS OF THE IMPLEMENTATION OF HAND HYGIENE EDUCATION IN HIGH SCHOOLS IN REDUCING THE INCIDENCE RATE OF INFECTIOUS DISEASES - Tjhia Khie Khiong (International Journal of Teaching and Learning, 2026)
This study aims to analyze the implementation of hand hygiene education in senior secondary schools (SMA) and its impact on reducing the incidence of infectious diseases among students. Through a literature review method, this research collects and analyzes data from various sources that describes hand hygiene education programs and their effectiveness in the context of high schools. The results of the analysis show that a hand hygiene education program implemented systematically and continuously is able to increase awareness and hand hygiene behavior among students. This program has also been proven to significantly reduce the incidence of infectious diseases, such as influenza, diarrhea and respiratory tract infections. This research highlights the importance of support from schools, educators, and families in maximizing the effectiveness of hand hygiene education programs. Apart from that, this research also emphasizes the need for adequate tools and facilities, such as soap and clean water, as well as providing consistent and precise information regarding the importance of hand hygiene. The conclusion of this research shows that implementing good hand hygiene education can be an effective strategy in reducing the incidence of infectious diseases in high schools. This research recommends that schools implement a comprehensive and sustainable approach to instilling good hand hygiene behavior among students.